Method for preparing MIL-88A (Fe)-melamine sponge in situ by pre-burying seeds and application of MIL-88A (Fe)-melamine sponge in oil-water separation

The method of preparing MIL-88A(Fe)@melamine sponge in situ by pre-burying seeds solves the problems of uneven coating and weak bonding of oil-water separation materials, achieving uniform coating and strong bonding of materials, and possessing high-efficiency oil-water separation performance and the ability to be recycled multiple times.

CN120944180APending Publication Date: 2025-11-14XINXIANG MEDICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511048479.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-29
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing oil-water separation materials suffer from uneven coating and weak bonding during the modification process, leading to decreased oil-water separation performance and fewer uses.

Method used

The method of in-situ preparation of MIL-88A(Fe)@melamine sponge by pre-embedded seeds introduces ferric ions as in-situ growth sites by crosslinking hydroxyl-terminated polydimethylsiloxane and ferric chloride on the surface of melamine sponge. Subsequently, MIL-88A(Fe) is synthesized in the MIL-88A(Fe) reaction system to achieve uniform coating and firm bonding of the material.

Benefits of technology

The prepared material has a uniform surface distribution, strong bonding, good oil-water separation capability, and can be recycled multiple times. It exhibits superhydrophobicity and superoleophilicity, and can efficiently separate light oil floating on the water surface and heavy oil sinking to the bottom.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120944180A_ABST
    Figure CN120944180A_ABST
Patent Text Reader

Abstract

The invention discloses a method for in-situ preparation of MIL-88A (Fe) melamine sponge by pre-burying seeds and application of the MIL-88A (Fe) melamine sponge in oil-water separation, and belongs to the technical field of separation materials and water treatment. The preparation method comprises the following steps: firstly, modifying the surface of melamine sponge (MS) by using hydroxyl-terminated polydimethylsiloxane (PDMS-OH), adding ferric trichloride to enable the surface-modified melamine sponge to be rich in iron ions based on the complexing action of the hydroxyl of the PDMS and metal ions, then putting the material into an MIL-88A (Fe) synthesis system, and growing the MIL-88A (Fe) on the surface by taking ferric ions as in-situ growth sites, so that the MIL-88A (Fe) / PDMS composite material is obtained. Oil-water separation is realized by using hydrophobicity of polydimethylsiloxane and MIL-88A (Fe), and chemical demulsification is realized by using mechanisms such as metal ions to destroy an interfacial film, so that a relatively good oil-water separation effect is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of separation materials and water treatment technology, and particularly relates to a method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds and its application in oil-water separation. Background Technology

[0002] Oil spills from the oil extraction industry, untreated oily wastewater from industry, and daily oil discharges from docks and submarines have, over time, had a significant impact on the ecological environment. While oil is currently an essential energy source for human technological development, the environmental hazards it causes cannot be ignored. The global oil extraction industry continues to develop, and oil spills continue to occur. In addition to controlling the source, it is also necessary to treat industrial wastewater and oil discharges from docks and submarines. Existing oil-water separation methods mainly include physical, chemical, and biological methods. Among them, physical adsorption has attracted attention in the field of oil-water separation due to its high efficiency, low energy consumption, and recyclability. By crosslinking materials with superhydrophobic / superoleophilic properties onto macroporous adsorbent materials, and utilizing the adsorption properties of the adsorbent materials and the superhydrophobic / superoleophilic properties of the superhydrophobic / superoleophilic materials, a good oil-water separation effect can be achieved.

[0003] Sponges, due to their high porosity, possess excellent adsorption capacity for both oil and water, and are commonly used as matrices for oil-water separation materials. By modifying the surface of sponges to achieve superhydrophobic / superoleophilic properties, adsorbent materials with good oil-water separation performance can be obtained. Materials commonly used for oil-water separation modification include animal hair, polymer materials, metal-organic frameworks (MOFs), and other composite materials. Among these, composite organosilicon materials, such as hydroxyl-terminated polydimethylsiloxane (PDMS-OH), have wide applications in oil-water separation due to their unique hydrophobic properties; metal-organic frameworks (MOFs) also have wide applications in adsorption due to their unique crystal structure and tunability. Polymerizing these materials with high oil-water separation performance through chemical reactions holds promise for obtaining materials with even better oil-water separation performance.

[0004] However, traditional synthesis methods, such as impregnation, involve preparing a solution of the modifier and then immersing the matrix in it. After a period of deposition and polymerization, the modifier adheres to the matrix surface, completing the modification. This method suffers from drawbacks such as uneven coating and weak bonding of the modifier, which can detach during oil-water separation, affecting the cyclic adsorption performance. Another method, chemical deposition, modifies the matrix by forming a solid film on the matrix surface through a chemical reaction. This method can be applied to various materials, and the resulting coating film has good density, low porosity, and relatively strong bonding with the matrix. However, it still suffers from drawbacks such as uneven distribution of the coating material on the matrix surface, which can significantly reduce the performance of the oil-water separation material and the number of uses.

[0005] Therefore, there is an urgent need for a method to prepare oil-water separation materials with good oil-water separation capabilities and the ability to be recycled multiple times in order to solve the above problems. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention proposes a method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds and its application in oil-water separation. This method overcomes the shortcomings of traditional synthesis methods in oil-water separation materials, such as uneven surface modification, poor dispersion, and unstable bonding between the matrix and the modified material.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] This invention provides a method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds, comprising the following steps:

[0009] (1) Melamine sponge was immersed in a mixed solution of hydroxyl-terminated polydimethylsiloxane solution and ferric chloride solution, and after stirring and drying, PDMS@melamine sponge rich in ferric iron was obtained.

[0010] (2) The PDMS@melamine sponge rich in ferric iron obtained in step (1) is placed in the MIL-88A(Fe) reaction system to react and obtain MIL-88A(Fe)@melamine sponge.

[0011] Technical Principle: This invention first modifies the surface of melamine sponge (MS) with hydroxyl-terminated polydimethylsiloxane (PDMS-OH). Based on the complexation effect of PDMS hydroxyl groups with metal ions, ferric chloride is added to enrich the surface-modified melamine sponge with iron ions. Then, the material is placed in the MIL-88A(Fe) synthesis system, and MIL-88A(Fe) is grown on the surface using ferric ions as in-situ growth sites. The hydrophobicity of polydimethylsiloxane and MIL-88A(Fe) is used to achieve oil-water separation, and chemical demulsification is achieved by means of metal ions destroying the interfacial film, thereby achieving a better oil-water separation effect.

[0012] Further, in step (1), the mass ratio of the hydroxyl-terminated polydimethylsiloxane in the melamine sponge solution to the ferric chloride in the ferric chloride solution is (1-100):1:1.

[0013] Further, in step (1), the solvent of the hydroxyl-terminated polydimethylsiloxane solution is n-hexane; and the solvent of the ferric chloride solution is ethanol.

[0014] Furthermore, in step (1), the stirring time is 10 minutes.

[0015] Furthermore, in step (2), the MIL-88A(Fe) reaction system is composed of ferric chloride solution and fumaric acid solution.

[0016] Further, in step (2), the mass ratio of the PDMS@melamine sponge rich in ferric trivalent iron, the ferric chloride in the ferric chloride solution, and the fumaric acid in the fumaric acid solution is (1-100):0.73:0.52.

[0017] Furthermore, the solvent for the ferric chloride solution is water; the solvent for the fumaric acid solution is ethanol.

[0018] Furthermore, in step (2), the reaction is carried out at room temperature for 12-14 hours.

[0019] The present invention also provides a MIL-88A(Fe)@melamine sponge, which is prepared according to the preparation method described in the above technical solution.

[0020] The present invention also provides an application of MIL-88A(Fe)@melamine sponge as described above in oil-water separation.

[0021] Compared with the prior art, the present invention has the following advantages and technical effects:

[0022] Pre-embedded seed in-situ growth technology refers to introducing in-situ growth sites on the surface of a carrier using a suitable cross-linking agent, then placing the carrier in a reaction system where the reactants react with the introduced sites, using these sites as growth points to synthesize the desired material. Pre-embedded seed in-situ polymerization utilizes the property of uniform distribution of substances in solution to uniformly introduce in-situ growth sites. This invention uses pre-embedded seeds to prepare MIL-88A(Fe)@melamine sponge in-situ. The synthesized material has a uniform surface distribution and strong bonding, ensuring not only good oil-water separation capabilities but also the ability to be recycled multiple times.

[0023] This invention uses melamine sponge as a matrix, crosslinking hydroxyl-terminated polydimethylsiloxane (PDMS-OH) onto its surface. The hydroxyl groups on the PDMS-OH surface crosslink with the amino groups on the melamine surface to coat the hydroxyl-terminated PDMS-OH onto the melamine sponge surface. The remaining silanol groups are used to introduce trivalent iron as in-situ growth sites. The modified material is then placed in a MIL-88A(Fe) synthesis system, allowing for the uniform synthesis of MIL-88A(Fe) on the melamine surface. This invention utilizes the surface-crosslinked MIL-88A(Fe) to achieve hydrophobic and oleophilic properties. The dried PDMS-OH coating further enhances its oil-water separation performance. The metal ions contained in MIL-88A(Fe) can also demulsify the interfacial membrane, resulting in an oil-water separation material that not only achieves simple oil-water separation but also exhibits good separation performance for emulsified oils.

[0024] When the MIL-88A(Fe)@melamine sponge prepared according to this invention is placed in water, it exhibits a silver mirror effect, indicating that the material has superhydrophobic properties. Furthermore, the MIL-88A(Fe)@melamine sponge prepared according to this invention has good adsorption properties for light oils such as n-hexane that float on the water surface and heavy oils such as chloroform that sink in water, enabling efficient oil-water separation. Attached Figure Description

[0025] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0026] Figure 1 This is a process flow diagram of the method for in-situ preparation of MIL-88A(Fe)@melamine sponge using pre-embedded seeds in Example 1;

[0027] Figure 2 SEM image (10 μm) of MS-PDMS-Fe prepared in Example 1;

[0028] Figure 3SEM image (100 μm) of MS-PDMS-Fe prepared in Example 1;

[0029] Figure 4 The elemental analysis chromatogram of MS-PDMS-Fe prepared in Example 1;

[0030] Figure 5 The elemental analysis chromatogram of C, O, Si, and Fe in MS-PDMS-Fe prepared in Example 1 is shown below.

[0031] Figure 6 The surface EDS energy spectrum of MS-PDMS-Fe prepared in Example 1;

[0032] Figure 7 Example 1: SEM image (40 μm) of MS-PDMS-MIL-88A;

[0033] Figure 8 SEM image (1 μm) of MS-PDMS-MIL-88A prepared for Example 1;

[0034] Figure 9 The infrared spectra of MS(a) and MS-PDMS-MIL-88A(b) in Example 1 are shown.

[0035] Figure 10 The images show the oil-water adsorption of MS and MS-PDMS-MIL-88A in Example 1, where the material on the left is MS and the material on the right is MS-PDMS-MIL-88A.

[0036] Figure 11 The silver mirror effect results are for MS-PDMS-MIL-88A prepared in Example 1;

[0037] Figure 12 A photograph of the physical sample used for hexane-water separation using MS-PDMS-MIL-88A prepared in Example 1;

[0038] Figure 13 A photograph of the chloroform-water separation performed using MS-PDMS-MIL-88A prepared in Example 1;

[0039] Figure 14 The water contact angles of MS and MS-PDMS-MIL-88A in Example 1;

[0040] Figure 15 The adsorption capacity of MS-PDMS-MIL-88A in Example 1 for different oil solvents;

[0041] Figure 16The effect of the number of cycles on the adsorption performance of MS-PDMS-MIL-88A in Example 1;

[0042] Figure 17 SEM image (100 μm) of the melamine sponge composite material prepared in Comparative Example 1;

[0043] Figure 18 SEM image (4 μm) of the melamine sponge composite material prepared in Comparative Example 1. Detailed Implementation

[0044] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0045] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0046] This invention provides a method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds, comprising the following steps:

[0047] (1) Melamine sponge was immersed in a mixed solution of hydroxyl-terminated polydimethylsiloxane solution and ferric chloride solution, and after stirring and drying, PDMS@melamine sponge rich in ferric iron was obtained.

[0048] (2) The PDMS@melamine sponge rich in ferric iron obtained in step (1) is placed in the MIL-88A(Fe) reaction system to react and obtain MIL-88A(Fe)@melamine sponge.

[0049] This invention uses melamine as the material matrix and introduces ferric iron as an in-situ growth site through PDMS-OH crosslinking. This is then placed in the MIL-88A(Fe) synthesis system to prepare MIL-88A@melamine sponge (MS-PDMS-MIL-88A). Melamine sponge is a three-dimensional porous material formed by the condensation of melamine and formaldehyde and a foaming process. Its open porosity can reach over 99%, thus exhibiting good elasticity and strong mechanical strength. Furthermore, due to its low production cost, light weight, and good chemical stability, it is widely used as a carrier for oil-water separation adsorption materials. When PDMS-OH is uncured, its surface has silanol groups and siloxanes. Silanol groups are strong active sites that can link the framework structure and organic materials, modifying the three-dimensional porous structure to achieve superhydrophobicity. After curing, the surface silanol groups disappear through condensation, and the methyl groups on the remaining siloxane branches exhibit strong hydrophobicity. MIL-88A(Fe) is a metal-organic framework (MOF) material synthesized from ferric chloride and fumaric acid. Due to its unique structure and tunability, it is widely used in the field of adsorption. The metal ions in the material play a demulsifying role through mechanisms such as neutralizing charges and disrupting interfacial films, and have a good effect on oil-water separation.

[0050] In a preferred embodiment, in step (1), the mass ratio of the melamine sponge, the hydroxyl-terminated polydimethylsiloxane in the hydroxyl-terminated polydimethylsiloxane solution, and the ferric chloride in the ferric chloride solution is (1-100):1:1, more preferably 20:1:1. This invention uses PDMS-OH to modify the surface of the melamine sponge. The hydroxyl groups on the PDMS-OH surface polymerize with the amino groups on the melamine surface, causing them to adhere, thus obtaining a sponge with a surface rich in silanol groups. Simultaneously, the addition of ferric chloride allows the ferric ions to combine with the remaining silanol groups in the PDMS-OH, achieving the purpose of linking ferric ions to MS through PDMS-OH.

[0051] In a preferred embodiment, in step (1), the solvent of the hydroxyl-terminated polydimethylsiloxane solution is n-hexane; the preparation method of the hydroxyl-terminated polydimethylsiloxane solution is as follows: take 0.05g of hydroxyl-terminated polydimethylsiloxane and dissolve it in 10mL of n-hexane to obtain the hydroxyl-terminated polydimethylsiloxane solution.

[0052] In a preferred embodiment, in step (1), the solvent of the ferric chloride solution is ethanol; the ferric chloride solution is prepared by dissolving 0.05g of anhydrous ferric chloride in 20mL of ethanol solution to obtain the ferric chloride solution; wherein, the mass concentration of the ethanol solution is 95%.

[0053] In a preferred embodiment, the stirring time in step (1) is 10 minutes. This invention achieves complete saturation of the melamine sponge through stirring. This invention does not impose any specific limitation on the stirring rate.

[0054] In a preferred embodiment, in step (1), the drying temperature is 60°C and the time is 6 hours.

[0055] In a preferred embodiment, in step (2), the MIL-88A(Fe) reaction system consists of ferric chloride solution and fumaric acid solution.

[0056] In a preferred embodiment, in step (2), the mass ratio of the ferric iron-rich PDMS@melamine sponge, the ferric chloride solution, and the fumaric acid solution is (1-100):0.73:0.52, more preferably 1:0.73:0.52. This invention uses the ferric iron introduced in step (1) as an in-situ growth site, and places the modified melamine sponge into the MIL-88A(Fe) reaction system for reaction, thereby preparing MIL-88A@melamine sponge.

[0057] In a preferred embodiment, the solvent of the ferric chloride solution is water; the ferric chloride solution is prepared by dissolving 0.73g of anhydrous ferric chloride in 30mL of water and dispersing it evenly by ultrasonication to obtain the ferric chloride solution.

[0058] In a preferred embodiment, the solvent of the fumaric acid solution is ethanol; the fumaric acid solution is prepared by dissolving 0.52g of fumaric acid in 30mL of ethanol solution, and then ultrasonically dispersing it evenly to obtain the fumaric acid solution; wherein, the mass concentration of the ethanol solution is 95%.

[0059] In a preferred embodiment, step (2) further includes a shaking step after placing the ferric iron-rich PDMS@melamine sponge obtained in step (1) into the MIL-88A(Fe) reaction system; the ferric iron-rich PDMS@melamine sponge is immersed below the liquid surface by shaking.

[0060] In a preferred embodiment, in step (2), the reaction is carried out at room temperature for 12-14 hours.

[0061] In a preferred embodiment, step (2) further includes drying and cleaning steps after the reaction is completed; the drying temperature is 30°C and the time is 12 hours; the cleaning agent is water, and the unreacted raw materials are removed by cleaning.

[0062] The present invention also provides a MIL-88A(Fe)@melamine sponge, which is prepared according to the preparation method described in the above technical solution.

[0063] The present invention also provides an application of MIL-88A(Fe)@melamine sponge as described above in oil-water separation.

[0064] In this embodiment of the invention, room temperature refers to "25±2℃".

[0065] The instruments used in the examples and comparative examples are shown in Table 1.

[0066] Table 1 Main Instruments

[0067] Instrument Name model Manufacturer Electronic analytical balance AUY220 Shimadzu Corporation Ultrasonic cleaner KQ3200E Kunshan Ultrasonic Instruments Co., Ltd. Heat-collecting intelligent magnetic stirrer SY20-2 Shanghai Sile Instruments Co., Ltd. Forced air drying oven DHG-9035A Shanghai Yiheng Scientific Instruments Co., Ltd.

[0068] The types, specifications, and sources of materials used in the examples and comparative examples are shown in Table 2.

[0069] Table 2 Main Materials

[0070]

[0071] Example 1

[0072] A method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds, the process flow diagram is shown below. Figure 1 The specific steps are as follows:

[0073] (1) Dissolve 0.05g of PDMS-OH in 10mL of n-hexane to obtain a PDMS-OH solution; dissolve 0.05g of anhydrous ferric chloride in 20mL of ethanol (95% by mass) to obtain a ferric chloride solution; mix the above PDMS-OH solution and ferric chloride solution to obtain a mixed solution; and take 1.0g of a 5*5*0.5cm sample. 3 The melamine sponge was placed in the above mixed solution and stirred to fully impregnate it. After 10 minutes, it was placed in a drying oven at 60°C and dried for 6 hours to obtain PDMS@melamine sponge (MS-PDMS-Fe) with a surface rich in ferric iron.

[0074] (2) Dissolve 0.73g of anhydrous ferric chloride in 30mL of water and disperse it evenly by ultrasonication to obtain a ferric chloride solution; dissolve 0.52g of fumaric acid in 30mL of ethanol solution (mass concentration of 95%) and disperse it evenly by ultrasonication to obtain a fumaric acid solution; mix the above ferric chloride solution and fumaric acid solution to obtain a MIL-88A(Fe) reaction system; put 1.0g of MS-PDMS-Fe obtained in step (1) into the above MIL-88A(Fe) reaction system, shake it so that MS-PDMS-Fe is immersed below the liquid surface, place it at room temperature for 13h, take it out, dry it at 30℃ overnight, and wash away the unreacted raw materials with water to obtain MIL-88A(Fe)@melamine sponge (MS-PDMS-MIL-88A).

[0075] Figure 2 SEM image (10 μm) of MS-PDMS-Fe prepared in Example 1. From Figure 2 It can be seen that a thin film is coated on the melamine backbone in the MS-PDMS-Fe prepared in Example 1, indicating that PDMS has a good coating effect on the surface of melamine sponge.

[0076] Figure 3 SEM image (100 μm) of MS-PDMS-Fe prepared in Example 1. Figure 4 The image shows the elemental analysis chromatogram of MS-PDMS-Fe prepared in Example 1. Figure 5 The image shows the elemental analysis of C, O, Si, and Fe in MS-PDMS-Fe prepared in Example 1. Figure 6 The surface EDS energy spectrum of MS-PDMS-Fe prepared in Example 1. From... Figures 4-6 It can be seen that silicon and iron elements were successfully adhered to and uniformly dispersed on the surface of melamine sponge, proving that ferric ions were introduced as in-situ growth sites.

[0077] Figure 7 Example 1: SEM image (40 μm) of MS-PDMS-MIL-88A. Figure 8 SEM image (1 μm) of MS-PDMS-MIL-88A prepared for Example 1. From Figure 7 It can be seen that MIL-88A(Fe) has a good coating effect on melamine, from Figure 8 The crystal structure of MIL-88A(Fe) can be seen.

[0078] The MS and MS-PDMS-MIL-88A samples in Example 1 were analyzed using an attenuated total reflectance Fourier transform infrared spectrometer (ATR-FTIR), and the results are as follows: Figure 9 As shown.

[0079] Figure 9 The images show the infrared spectra of MS(a) and MS-PDMS-MIL-88A(b) from Example 1. Figure 9 As can be seen, compared with the blank melamine sponge (MS), MS-PDMS-MIL-88A showed better performance at 1395cm. -1 1605cm -1 3086cm -1 The peak intensity at 1395 cm⁻¹ increased significantly. -1 The peak at 1605 cm⁻¹ is likely due to the in-plane bending vibration of CH in MIL-88A(Fe). -1 The peak at 3086 cm⁻¹ is likely the stretching vibration peak of the C=C double bond in MIL-88A(Fe). -1 The increase in peak value may be due to the hydroxyl groups in the carboxylic acid of MIL-88A(Fe) and the effect of water adsorption by the sponge. From the above analytical results, it can be concluded that the present invention polymerizes MIL-88A(Fe) in situ on the surface of melamine.

[0080] Performance testing

[0081] 1. Wetting properties

[0082] Water and n-hexane (stained with Sudan III) were added dropwise to the surfaces of MS and MS-PDMS-MIL-88A in Example 1, respectively, and the oil and water adsorption on the material surfaces was observed. The results are shown in [Figure 1]. Figure 10 .

[0083] Figure 10 The images show actual oil-water adsorption of MS and MS-PDMS-MIL-88A in Example 1, where the material on the left is MS and the material on the right is MS-PDMS-MIL-88A. Figure 10 As can be seen, the melamine sponge MS exhibits good adsorption performance for both water and oil (n-hexane, stained with Sudan III) (the melamine sponge MS appears gray after adsorbing water droplets because the desktop is black). In contrast, the material MS-PDMS-MIL-88A synthesized in this invention not only shows good adsorption performance for oil (n-hexane, stained with Sudan III) but also exhibits strong hydrophobic effects, indicating that the MIL-88A(Fe)@melamine sponge prepared in this invention exhibits good hydrophobic and oleophilic properties.

[0084] 2. Hydrophobic and oleophilic

[0085] The MS-PDMS-MIL-88A prepared in Example 1 was placed in water, and the hydrophobicity of the material surface was observed. The results are shown below. Figure 11 .

[0086] Figure 11The silver mirror effect results are shown for MS-PDMS-MIL-88A prepared in Example 1. From... Figure 11 As can be seen, when MS-PDMS-MIL-88A prepared in Example 1 is placed in water, the water cannot wet its surface due to its hydrophobic surface, so the material surface will exhibit a "silver mirror effect", that is, the water will generate bubbles due to the hydrophobicity and thus produce a refractive effect, which shows the superhydrophobicity of the material.

[0087] Because oil contamination is diverse, to demonstrate the superlipophilicity of the material of this invention, tests were conducted on two oily substances with different properties: light oil n-hexane (stained with Sudan III) that floats on the water surface and heavy oil chloroform (stained with Sudan III) that sinks in water. The results are shown in [Figure number missing]. Figure 12 and Figure 13 .

[0088] Figure 12 This is a photograph of the n-hexane-water separation process using MS-PDMS-MIL-88A prepared in Example 1. Figure 13 This is a photograph of the chloroform-water separation process using MS-PDMS-MIL-88A prepared in Example 1. Figure 12 and Figure 13 It can be seen that MS-PDMS-MIL-88A has good adsorption performance for both light and heavy oil, indicating that MS-PDMS-MIL-88A synthesized by in-situ polymerization with pre-embedded seeds has good oil-water separation performance.

[0089] 3. Oil-water separation performance

[0090] Figure 14 The water contact angles for MS and MS-PDMS-MIL-88A in Example 1. From Figure 14 It can be seen that the original melamine sponge has a high affinity for water. Once water comes into contact with the sponge, it is absorbed within 0.25s, and the water contact angle is zero. However, the water contact angle of the modified MS-PDMS-MIL-88A is significantly increased to 144.02°.

[0091] To further evaluate the adsorption capacity of the material, adsorption capacity is used. After a unit of material has adsorbed sufficient oil, it is weighed, the adsorption amount is calculated, and the material's adsorption performance is assessed. The method for calculating the adsorption amount is as follows:

[0092] Q = (m2-m1) / m1 × 100%;

[0093] In the formula: m2 is the mass of MS-PDMS-MIL-88A after adsorption, g; m1 is the mass of MS-PDMS-MIL-88A before adsorption, g; Q is the adsorption amount, g / g.

[0094] Figure 15The adsorption capacity of MS-PDMS-MIL-88A in Example 1 for different oil solvents. Figure 15 As can be seen, MS-PDMS-MIL-88A has good oil and water adsorption performance, with an adsorption capacity for oily substances ranging from 34.76 g / g to 62.67 g / g. Among them, the adsorption capacity for chloroform can reach 62.67 g / g, showing good superlipophilic properties.

[0095] 4. Number of loops

[0096] After sufficient n-hexane was adsorbed using MS-PDMS-MIL-88A in Example 1, the sponge was squeezed with tweezers until no more adsorbed n-hexane could be expelled. Then, it was dried in an oven at 30°C, and the adsorption of n-hexane was repeated. The adsorption amount was tested every 10 cycles, and the results are shown below. Figure 16 .

[0097] Figure 16 The effect of the number of cycles on the adsorption performance of MS-PDMS-MIL-88A in Example 1 was investigated. Figure 16 As can be seen, after 50 cycles, MS-PDMS-MIL-88A still exhibits good adsorption performance for n-hexane, fully meeting industrial application requirements. After 50 cycles, the adsorption capacity remains at 70% of the initial adsorption capacity. These results demonstrate that MS-PDMS-MIL-88A possesses good oil adsorption capacity and recyclability.

[0098] Comparative Example 1

[0099] A method for preparing a melamine foam composite material, the specific steps of which are as follows:

[0100] (1) Dissolve 0.05g of PDMS-OH in 10mL of n-hexane to obtain a PDMS-OH solution; dissolve 1.0g of PDMS-OH in 10mL of n-hexane to obtain a PDMS-OH solution; 3 The melamine sponge was placed in the above PDMS-OH solution and stirred to ensure complete immersion. After 10 minutes, it was placed in a drying oven at 60°C and dried for 6 hours to obtain PDMS@melamine sponge (MS-PDMS).

[0101] Step (2) is the same as in Example 1.

[0102] Figure 17 SEM image (100 μm) of the melamine sponge composite material prepared in Comparative Example 1. Figure 18 SEM image (4 μm) of the melamine sponge composite material prepared in Comparative Example 1. Figure 17 and Figure 18It can be seen that, since no seeds were pre-embedded in Comparative Example 1, no MIL-88A(Fe) was observed on the surface of the melamine sponge composite material.

[0103] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds, characterized in that, Includes the following steps: (1) Melamine sponge was immersed in a mixed solution of hydroxyl-terminated polydimethylsiloxane solution and ferric chloride solution, and after stirring and drying, PDMS@melamine sponge rich in ferric iron was obtained. (2) The PDMS@melamine sponge rich in ferric iron obtained in step (1) is placed in the MIL-88A(Fe) reaction system for reaction to obtain MIL-88A(Fe)@melamine sponge.

2. The method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds according to claim 1, characterized in that, In step (1), the mass ratio of the hydroxyl-terminated polydimethylsiloxane in the melamine sponge solution to the ferric chloride in the ferric chloride solution is (1-100):1:

1.

3. The method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds according to claim 1, characterized in that, In step (1), the solvent for the hydroxyl-terminated polydimethylsiloxane solution is n-hexane; the solvent for the ferric chloride solution is ethanol.

4. The method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds according to claim 1, characterized in that, In step (1), the stirring time is 10 minutes.

5. The method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds according to claim 1, characterized in that, In step (2), the MIL-88A(Fe) reaction system consists of ferric chloride solution and fumaric acid solution.

6. The method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds according to claim 5, characterized in that, In step (2), the mass ratio of the PDMS@melamine sponge rich in ferric trivalent iron, ferric chloride in the ferric chloride solution, and fumaric acid in the fumaric acid solution is (1-100):0.73:0.

52.

7. The method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds according to claim 5, characterized in that, The solvent for the ferric chloride solution is water; the solvent for the fumaric acid solution is ethanol.

8. The method for in-situ preparation of MIL-88A(Fe)@melamine sponge with pre-embedded seeds according to claim 1, characterized in that, In step (2), the reaction is carried out at room temperature for 12-14 hours.

9. A MIL-88A(Fe)@melamine sponge, characterized in that, It is prepared according to any one of claims 1-8.

10. The application of the MIL-88A(Fe)@melamine sponge as described in claim 9 in oil-water separation.